Ectopic expression of TaOEP16-2-5B, a wheat plastid outer envelope protein gene, enhances heat and drought stress tolerance in transgenic Arabidopsis plants. (May 2017) - Zang, Xinshan; Geng, Xiaoli; Liu, Kelu; Wang, Fei; Liu, Zhenshan; Zhang, Liyuan; Zhao, Yue; Tian, Xuejun; Hu, Zhaorong; Yao, Yingyin; Ni, Zhongfu; Xin, Mingming; et al.
Highlights: The wheat homolog of Arabidopsis OEP16-2, designated TaOEP16-2, was upregulated under heat and drought stress conditions. Three homoeologous sequences of TaOEP16-2 were isolated from hexaploid wheat, which were localized on the chromosomes 5A, 5B and 5D, respectively. Ectopic expression of TaOEP16-2 - 5B in Arabidopsis enhances heat and drought stress tolerance. Abstract: Abiotic stresses, such as heat and drought, are major environmental factors restricting crop productivity and quality worldwide. A plastid outer envelope protein gene, TaOEP16-2, was identified from our previous transcriptome analysis[1, 2] . In this study, the isolation and functional characterization of the TaOEP16-2 gene was reported. Three homoeologous sequences of TaOEP16-2 were isolated from hexaploid wheat, which were localized on the chromosomes 5A, 5B and 5D, respectively. These three homoeologues exhibited different expression patterns under heat stress conditions, TaOEP16-2 - 5B was the dominant one, and TaOEP16-2 - 5B was selected for further analysis. Compared with wild type (WT) plants, transgenic Arabidopsis plants overexpressing the TaOEP16-2 - 5B gene exhibited enhanced tolerance to heat stress, which was supported by improved survival rate, strengthened cell membrane stability and increased sucrose content. It was also found that TaOEP16-2 was induced by drought stress and involved in drought stress tolerance. TaOEP16-2-5B has the same function in ABA-controlled seed germination as AtOEP16-2 . Our results suggest that TaOEP16-2-5B plays an important role in heat and drought stress tolerance, and could be utilized in transgenic breeding of wheat and other crop plants.